1403. Daptomycin Combined with Low Dose Ceftriaxone Prevents the Emergence of Daptomycin Resistance against Streptococcus mitis-oralis Group in an In vitro Model of Simulated Endocardial Vegetations (SEVs). (26th November 2018) - Kebriaei, Razieh; Rice, Seth; Stamper, Kyle; Garcia-De-La-Maria, Cristina; Mishra, Nagendra; Miro, Jose M; Arias, Cesar; Tran, Truc; Sullam, Paul; Bayer, Arnold; Rybak, Michael J
Abstract: Background: The viridans group streptococci (VGS) are a heterogeneous group of microorganisms that form portion of the normal oral flora of humans. Among the VGS, S. mitis-oralis is the most common cause of infective endocarditis in the developing world, as well as the leading cause of the "toxic Strep syndrome" in neutropenic cancer patients. Therapeutic options are often limited by frequent β-lactam resistance, as well as vancomycin tolerance. Daptomycin (DAP) has been suggested as an alternative therapeutic option for invasive S. mitis-oralis infections. However, the ability of these strains to rapidly evolve high-level and durable DAP-resistance (DAP-R) is problematic. Recent data have suggested the potential for combined DAP +β-lactam therapy to circumvent this issue. Methods: Using human-simulated dosing, the activities of DAP (6, 8, 10 or 12 mg/kg/day × 4 days) alone vs. DAP (6 mg/kg/day) +(CRO) (500 mg daily × 4 days or 500 mg, given once on day one) were assessed against two DAP-susceptible (DAP-S) S. mitis-oralis strains (SF100; 351) employing a PK-PD model of simulated endocardial vegetations (SEVs). Results: DAP alone was not bactericidal at any dose-regimen, and regrowth of high-level DAP-R isolates was observed in both strains (MIC increase from 0.5 to >64 µg/mL). Combinations of DAP +CRO at either dose-regimen yielded significant reductions in log10 CFU/g amounts within SEVs for both strains (~6 log10 CFU/g and to detection limits) within 24 hours. In addition, no DAP-R strains were detected in either DAP+ CRO combination regimens over the 96-hour exposure period. Conclusion: Combinations of DAP+ low-dose CRO (even single dosing) showed promise to forestall the emergence of DAP-R in S. mitis-oralis strains. Such regimens can potentially lead to optimizing treatment outcomes with DAP therapy, with minimal β-lactam exposures. Further research in relevant in vivo models and clinically is warranted to determine the most optimized DAP+ CRO dose-regimens for the prevention of emergence of DAP-R among S. mitis-oralis strains. Disclosures: J. M. Miro, Abbvie: Consultant and Grant Investigator, Consulting honoraria and Research grant; Bristol-Myers Squibb: Consultant and Grant Investigator, Consulting honoraria and Research grant; Genentech: Consultant and Grant Investigator, Consulting honoraria and Research grant; Medtronic: Consultant and Grant Investigator, Consulting honoraria and Research grant; Novartis: Consultant and Grant Investigator, Consulting honoraria and Research grant; Gilead Sciences: Consultant and Grant Investigator, Consulting honoraria and Research grant; Pfizer: Consultant and Grant Investigator, Consulting honoraria and Research grant; ViiV Healthcare: Consultant and Grant Investigator, Consulting honoraria and Research grant. C. Arias, Merck & Co., Inc.: Grant Investigator, Research support; MeMed: Grant Investigator, Research support; Allergan: Grant Investigator, Research support. A. Bayer, Trellis: grant recipient, Grant recipient; Contrafect: grant recipient, Grant recipient; Theravance: grant recipient, Grant recipient. M. J. Rybak, Allergan: Consultant, Grant Investigator and Speaker's Bureau, Research grant and Research support; Achaogen: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Bayer: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Melinta: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Merck: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Theravance: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Sunovian: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; Zavante: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support; NIAID: Consultant, Grant Investigator and Speaker's Bureau, Consulting fee, Research grant and Research support.